Islamic counting game / Zanirah Mustafa@Busu … [et al.] - Mustafa@Busu, Zanirah; Nik Din, Nik Muniyati; Awang@Ab Rahman, Nurul Hidayah; Noor Zainan, Nurul Izzah; Mohd Firdaus Kozako, Intan Nurul'ain; Mat Jusoh, Nor Asmira; Junoh, Noraini; Yusuf, Norazmila; Musa, Muhammad Fadhli; Ismail, Mohd Khairul Anuar (2022)
In Islam, accounting is a crucial knowledge to obtain. It is a fundamental social practice that records financial reports on all activities. Accounting reports are instrumental especially for individuals who are involved in financial and accounting activities. At the same time, accounting reports are important for organizations and societies as well. As practiced at various financial institutions, the calculation methods involved in the Fundamental of Islamic Accounting course are complex and elaborate with different principles and formulas. Therefore, students found it difficult to understand and memorize all possible formulas hence require new teaching and learning tools to facilitate their learning. Teaching and learning aids are highlighted as one of the most recent transformations in computational learning in Islamic accounting. The primary objective of this study was to determine the efficacy of learning accounting in the classroom through the interactive application of the Islamic accounting mobile game (IAMG). Related data information for the research was obtained through the literature search and documentation of observations. Demographic and descriptive methods were utilized through research surveys, observations, and questionnaires on students. The results indicated that the majority of students were not aware of the IAMG application. Yet, interestingly after using IAMG, students felt that IAMG is influential and useful in their studies. The findings showed that the product is accepted by the students and had positive effects on the students and society.